2007
DOI: 10.1159/000101755
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Genetic Diagnosis in Pakistan: A Survey of Medical and Legal Communities and Parents of Thalassemic Children

Abstract: Objectives: It was the aim of this study to assess the attitudes of doctors, medical students, lawyers, parliament members and parents of thalassemic children towards genetic diagnosis in Pakistan. Study Design: A cross-sectional descriptive survey was conducted among representative samples. Results: Five hundred and seventy doctors, 49 lawyers, 178 medical students, 89 parents of thalassemic children and 16 members of parliament (MPs) were included in the survey. The groups showed considerable difference in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The acceptance rate was 90.3 % in Iran (Karimi et al 2010) and 75.2 % in Pakistan (Gilani et al 2007). Recent studies on Muslim populations revealed that education about the religion's stance on termination of pregnancy improved uptake of prenatal diagnosis and termination of pregnancies affected by thalassaemia and sickle cell anaemia (Alkuraya and Kilani 2001;Ahmed et al 2000).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The acceptance rate was 90.3 % in Iran (Karimi et al 2010) and 75.2 % in Pakistan (Gilani et al 2007). Recent studies on Muslim populations revealed that education about the religion's stance on termination of pregnancy improved uptake of prenatal diagnosis and termination of pregnancies affected by thalassaemia and sickle cell anaemia (Alkuraya and Kilani 2001;Ahmed et al 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Most of the successful thalassaemia preventive strategies incorporated prenatal diagnosis and selective termination of affected foetuses into their programmes. Studies addressing the acceptance of these measures have been done in Muslim-majority countries such as Iran (Karimi et al 2010), Pakistan (Gilani et al 2007), Lebanon (Zahed and Bou-dames 1997) and Saudi Arabia (Alkuraya and Kilani 2001) but are relatively scarce in Malaysia. A Malaysian survey among the general lay public documented not only a low level of knowledge about thalassaemia but it revealed that only 36.6 % of participants accepted selective termination of affected foetuses (Wong et al 2011) with the Malays less likely to accept abortion compared to the Chinese and Indians.…”
Section: Introductionmentioning
confidence: 99%
“…Gilani and colleagues questioned medical practitioners, lawyers, politicians and parents of children affected by thalassaemia in Pakistan, to determine people's attitudes about thalassaemia carrier screening. 47 Over 95% of the parents and 90% of the doctors supported genetic screening; however, only one-third of politicians were in favour of screening. 47 Thalassaemia screening has not yet been introduced in Sri Lanka; however, 96% of people agreed that at least one person in a marriage should undergo thalassaemia screening.…”
Section: Mandatory Screeningmentioning
confidence: 99%
“…47 Over 95% of the parents and 90% of the doctors supported genetic screening; however, only one-third of politicians were in favour of screening. 47 Thalassaemia screening has not yet been introduced in Sri Lanka; however, 96% of people agreed that at least one person in a marriage should undergo thalassaemia screening. 48 Outcomes of thalassaemia carrier screening Reduced incidence.…”
Section: Mandatory Screeningmentioning
confidence: 99%
“…Similarly, Gilani et al (2007), who investigated the attitude of medical practitioners and other stakeholders toward genetic screening for thalassemia, observed that, in 26 % of those that did not accept genetic screening, fear of discrimination and, in 30 %, individual stress was the stated reason. Other studies investigating the attitude of health care practitioners toward hemoglobinopathy screening showed a fairly positive attitude mainly predicted by subjective or social norm.…”
Section: Discussionmentioning
confidence: 99%